Relating environmental comfort conditions to student satisfaction with remote learning: A case on design students - Giresun Erdogan, Buket; Kutsal, Simge (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2023)
Remote learning applications have crucial importance in preventing education processes from being interrupted under extreme conditions such as a pandemic. Numerous studies on the field are being performed, as it is thought that remote learning will become even more critical in time. Notably, the variety of built environments in different regional, social, cultural, and technological aspects encourages researchers to investigate such differences and student performance and satisfaction relating to their conditions. Focusing on design students, who may have more distinct requirements since the nature of the education program they are subject to, this article aims to present the comfort conditions of students, as well as the relationship of such conditions with the level of student satisfaction with remote learning. The method of this study includes a comprehensive survey, which has been delivered to architecture and interior architecture students via online channels, questioning their spatial, visual, auditory, and thermal comfort. The multiple regression analysis, which has been used in connecting comfort conditions and satisfaction, has resulted that the built environment has a slight yet significant effect on satisfaction level (R=0.374). This result is substantial considering the variety and complexity of factors affecting satisfaction with remote learning. Findings of this study include that visual comfort conditions are the most influential on student satisfaction, indicating the inference that improvements relating to these conditions will be quite effective. The results of this study provide a perspective for improving remote learning processes and adapting living environments to remote learning, based on different student groups.
Keywords: Auditory comfort; remote learning; spatial comfort; thermal comfort; visual comfort; QUALITY; CLASSROOMS; EDUCATION; PERFORMANCE; HEALTH; Architecture